Knowledge-seeking and knowledge sharing of health services across social networks and communities: a scoping review - Anamitra Bhowmick; Marieke M. van der Zande; Rebecca Harris (BMC Health Services Research)
Abstract Introduction Lay people’s knowledge influences healthcare service utilisation, but the literature on people’s knowledge-seeking and sharing about different healthcare services across social networks is patchy and not well integrated. This scoping review was undertaken to map how different studies report healthcare service -related (healthcare) knowledge-seeking or sharing in social circles and to identify evidence gaps for further research. Method Levac’s enhanced scoping review framework was adapted to develop a comprehensive electronic search strategy. Four electronic databases-Medline, Web of Science, PsychINFO, and CINAHL were searched as well as Grey literature. Five per cent of all titles and abstracts screened were screened by a blinded second reviewer. After full-text screening, data were extracted and summarised. Results The review included 14 quantitative, 23 qualitative, 2 mixed-method studies, one literature review and one report [N = 41]. Theories included within studies ranged from the socio-ecological model to bricolage. The concept of healthcare-related knowledge was generally ill defined and usually positioned within the concept of health literacy more generally. Lay people’s healthcare knowledge was not generally considered as a distinct entity in a holistic sense, with only two studies identified which investigated healthcare knowledge exclusively at inter-personal (meso) levels. However, included studies showed that people’s healthcare knowledge in everyday life is co-constructed when they engage in inter-personal interactions with informal social network ties. People tend to acquire healthcare knowledge from others who share similar lived experiences of using healthcare services, which binds the knowledge seekers through homophily. Due to the social responsibility to help others being ingrained within the community, people (predominantly women), support each other, providing emotional and instrumental support in addition to essential healthcare information. This then builds holistic healthcare literacy, which people conventionally do not gain solely from the knowledge transmitted by healthcare professionals. Conclusion People in diverse community settings acquired, co-constructed, transmitted, or suppressed knowledge about various healthcare services with the support of informal networks, mostly family and friends, combined with mass media sources. Therefore, people’s healthcare knowledge is not an individual asset but a shared resource among their social circles. It is multi-faceted and acquired from diverse sources available in the local and online communities and not limited only to individually held lay accounts of using healthcare services.